Interpersonal problems among psychiatric outpatients and non-clinical samples - Tinakon Wongpakaran (2018)
INTRODUCTION The aims of this study were two-fold; to investigate the validity and reliability of the Thai version of the Inventory of Interpersonal Problems (IIP) and to compare the characteristics of the interpersonal problems experienced in a non-clinical sample and psychiatric outpatients. MeThODs A total of 689 subjects (452 non-clinical sample and 237 psychiatric outpatients) completed the IIP-32 and IIP-64, Symptom checklist-90 (SCL-90) and 16 Personality Factor (16 PF) Questionnaire, after which a four-week retest was carried out. Cronbach's alpha was used for internal consistency and the intra-class correlation coefficient was used to determine test-retest reliability. Factor analysis of the IIP sub-scales and Pearson's correlation were used for construct and concurrent validity. ResUlTs Both versions of the IIP showed good internal consistency. Factor analysis revealed two factors that corresponded to the circumplex property. The expected correlation between the SCL-90 and 16 PF subscales reflected the level of concurrent validity. There was a significant difference in the cold, socially-inhibited and self-sacrificing sub-scales between the non-clinical and clinical samples, while major depressive disorder was found to have a significantly higher score in the subscales of the control dimension, i.e. the non-assertive, socially inhibited and self-sacrificing sub-scales, than the neurotic and non-clinical groups, whereas, the neurotic group differed from the normative sample in terms of the affiliation axis. CONClUsION The IIP-64 and IIP-32 demonstrated their reliability and are suitable for use in either clinical or non-clinical setting.